2018
DOI: 10.7755/fb.116.2.3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutrients from carcasses of sea lamprey (Petromyzon marinus) on larval growth and spawner abundance

Abstract: Abstract-Migrations of anadromous sea lamprey (Petromyzon marinus) from marine ecosystems serve as vectors of nutrients into freshwater food webs. Larval sea lamprey reside in streams for 6-8 years as deposit feeders before metamorphosing into juveniles and migrating to the ocean. Previous work has shown that carcass nutrients, which result from the death of adult lamprey after spawning, increase stream productivity and are consumed by larvae. This may increase larval growth rates and enhance earlier metamorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The variability associated with the duration of the larval period (2–12 years) may be explained by the productivity of the inhabited waters (Dawson, Quintella, Almeida, Treble, & Jolley, ; Potter, ; Purvis, ). Weaver, Coghlan, and Zydlewski () explored the hypothesis that larval sea lamprey growth and metamorphosis are manipulated by changes in productivity invoked by subsidies of adult carcass nutrients. Thus, the exchange of nutrients and material by sea lamprey may alter the reciprocation of the subsidy between marine and freshwater ecosystems through population level changes among larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The variability associated with the duration of the larval period (2–12 years) may be explained by the productivity of the inhabited waters (Dawson, Quintella, Almeida, Treble, & Jolley, ; Potter, ; Purvis, ). Weaver, Coghlan, and Zydlewski () explored the hypothesis that larval sea lamprey growth and metamorphosis are manipulated by changes in productivity invoked by subsidies of adult carcass nutrients. Thus, the exchange of nutrients and material by sea lamprey may alter the reciprocation of the subsidy between marine and freshwater ecosystems through population level changes among larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed subsidies of MDN from anadromous fish increase the primary productivity of freshwater ecosystems through the bottomup pathway of nutrient incorporation. In temperate regions, where freshwater ecosystems are less productive than marine ecosystems, MDN from anadromous species transfers nutrients to freshwater ecosystems increasing their primary productivity (Wipfli et al, 2010;Weaver et al, 2016;Weaver et al, 2018a). In the Penobscot River basin, both bottom-up and top-down pathways of MDN incorporation in freshwater ecosystems have been studied experimentally through carcass addition and theoretically through modeling (Guyette et al, 2013;Guyette et al, 2014;Weaver et al, 2015;Weaver et al, 2016;Weaver et al, 2018b;Weaver et al, 2018c;Zydlewski et al, 2021).…”
Section: Seventh: Loss Of Ecosystem Servicesmentioning
confidence: 99%
“…Northwestern Atlantic freshwater ecosystems are generally nutrient-poor, and there is relatively little information describing MDN dynamics for these systems. However, recent field studies have demonstrated that when rivers are enriched with MDN from diadromous fishes, the impacts include: changes in biofilm standing stock and productivity (Walters et al, 2009;Weaver et al, 2017), increased macroinvertebrates composition and abundance Samways et al, 2017;Weaver et al, 2018a), and increased juvenile fish growth (Guyette et al, 2013;Weaver et al, 2016Weaver et al, , 2018bSamways et al, 2017). MDN have also been shown to directly (consumption of diadromous fishes) and indirectly (consumption of prey that consumed diadromous fishes) benefit various avian species (Dalton et al, 2009;Call, 2015).…”
Section: Nutrient Cyclingmentioning
confidence: 99%